Pharmaceutical analysis a textbook for pharmacy students and pharmaceutical chemists - Watson, David G., 1952- (Elsevier Churchill Livingstone, 2012)
This introductory text highlights the most important aspects of a wide range of techniques used in the control of the quality of pharmaceuticals. Written with the needs of the student in mind, this clear, practical guide includes self-testing sections with arithmetical examples and tests to help students brush up on their arithmetical skills in an applied context.